Botswana unemployment rate trends by gender: Relative analysis with upper middle income Southern African countries (2000-2016) - Mufaro Andrew Matandare (Dutch Journal of Finance and Management, 2018)
This paper analyses Botswana labour market trends, specifically unemployment rate, over a period between 2000 and 2016. Furthermore, a comparison with Namibia and South Africa is done. To make an inference on unemployment rate by age and gender, it is vital to both consider the development and changes in the labour market over time. Botswana's unemployment rate was found to average 18.2% between 2000 and 2016. However a disparity between male and female unemployment rate was observed. Youth unemployment rate has been increasing over the study period in Botswana. Furthermore, youth unemployment in Botswana surpassed total unemployment in 2016. Botswana was found to have a more stable labour market in comparison with Namibia and South Africa. However, South Africa was commended for having the lowest female youth unemployment rate as compared to Botswana and Namibia. The findings further discerned an increase in economically active populace in all the countries. The paper suggests policies geared at easing entry into the labour market for youth especially females as well as for women. Diversification and investment in labour intensive industries should be a priority. Governments are also challenged to invest in relevant training and skills development which meets employers' needs.
Keywords: 650; unemployment rate; labour market; Botswana; Namibia; South Africa